1974
DOI: 10.1084/jem.139.6.1464
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Tolerance in Bone Marrow-Derived Lymphocytes

Abstract: The present studies were designed to probe the role(s) of T cells in preventing or altering tolerance induction in hapten-specific B cells. This was accomplished by using hapten conjugates of normally immunogenic heterologous carriers to selectively inhibit 2,4-dinitrophenyl (DNP)-primed B cells in adoptive transfer experiments in vivo. The data provide strong indications that one critical role of T-cell participation in humoral responses to antigens is to circumvent the development of a tolerogenic signal tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1974
1974
2009
2009

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…However, the efficiency, kinetics, and duration of tolerance induction in vivo has always been of considerably greater magnitude than tolerance induced in vitro in our hands (3). Moreover, data will be presented in the following paper which documents a similar situation with tolerance induced in vivo with immunogenic molecules such as DNP-OVA under proper conditions (18). Finally, it should be pointed out that the experiments presented herein are representative of three-four experiments of each type, which all reproduce these basic observations quite consistently.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…However, the efficiency, kinetics, and duration of tolerance induction in vivo has always been of considerably greater magnitude than tolerance induced in vitro in our hands (3). Moreover, data will be presented in the following paper which documents a similar situation with tolerance induced in vivo with immunogenic molecules such as DNP-OVA under proper conditions (18). Finally, it should be pointed out that the experiments presented herein are representative of three-four experiments of each type, which all reproduce these basic observations quite consistently.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, the fact that DNP-OVA-treated cells were initially unresponsive but could be reversed by trypsinization appeared to point out at least a second distinct type of tolerance mechanism in B cells whereby transient unresponsiveness occurred due to surface receptor "blockade" presumably resulting from the binding of specific determinants by B cells in the absence of a suitable T-cell influence. The latter issue is, indeed, an important one which is considered in greater depth in the accompanying manuscript (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased susceptibility of nonresponder spleen cells to tolerance induction could be explained by the absence of GATspecific helper T-cell function. It has indeed been shown that spleen cells in the absence of activated helper T cells are easily tolerized (14,15). We have also shown that GAT-specific helper function cannot be demonstrated in nonresponder mice immunized with GAT.…”
Section: Discussionmentioning
confidence: 70%
“…As shown in Fig. 3 and in the accompanying paper (13) It has been demonstrated that B cells are more readily rendered unresponsive by antigens in the absence of specific helper T cells (14,15). Thus, it is possible to argue that the nonresponder B cells in the previous experiment were rendered tolerant to GAT while responder B cells were not, since the responder B cells were influenced by GAT-specific helper cell activity from the F~ T cells, whereas nonresponder B cells may be influenced only by MBSA helper T-cell activity.…”
Section: Sensitivity Of Spleen Cells To Tolerance Induction As a Funcmentioning
confidence: 95%